Free DNA, a reason for severe COVID-19 infection? (2020)
The fast-growing outbreak of 2019 novel coronaviruses (SARS-CoV-2) reached all continents except the Antarctica in merely three months. Severe SARS-CoV-2 infection (COVID-19) has a bad clinical outcome, and some reports emphasized the role of cytokine storm and dysfunctions of multiple organs. However, the etiology of severe COVID-19 has been largely unknown. Similar as SARS-CoV and MERS-CoV, SARS-CoV-2 is also thought derived from bat coronaviruses. However, it is not pathogenic for bat at all, because free DNA in cytoplasm or blood cannot bring up violent immune response in bat; but it can produce severe inflammations in human. I hypothesized that the damage induced by free DNA is a reason for severe COVID-19, which can explain many symptoms of this disease, such as cytokine storm, acute respiratory distress syndrome (ARDS) and muscus plug, acute injuries of heart, liver and kidney, and some special symptoms of COVID-19. My hypothesis will be helpful for better understand the etiology of severe COVID-19.